MEMPROGRAMKAN PENGENALAN BANK SYARIAH DAN LEMBAGA KEUANGAN MIKRO SYARIAH DI DESA DUKUH, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Rully Trihantana; Ria Kusumaningrum; Siska Oktavia (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
Islamic Micro Finance Institutions (LKMS) can be one of the parties that help efforts to improve the economy of small and medium communities in Indonesia. This LKMS provides microfinance instruments and products that are based on norms and values in Islamic finance and are relatively easier than Islamic banking institutions. However, there are still many who do not know about the existence of LKMS, and there are still many who are not familiar with Islamic banks. In this regard, this community service activity is carried out to use Islamic banks and LKMS to the community, especially the people in Dukuh Village, Cibungbulang District, Bogor Regency.